Analisis Penanganan Foreign Object Damage (FOD) di Apron Bandar Udara Internasional Yogyakarta Kulon Progo - Ratna Sari Dewi; Herida Panji Olivia Azhar (Manajemen Kreatif Jurnal, 2023)
Foreign Object Damage (FOD) is any object found in an inappropriate location that could damage equipment or injure personnel by virtue of being in that location.FOD includes a wide range of materials, including loose hardware, pavement fragments, catering supplies, building materials, stone , sand, luggage, and even wild animals. The aim of this research is to find out the handling of Foreign Object Damage at the Yogyakarta Kulon Progo International Airport Apron and to find out the factors that cause Foregin Object Damage (FOD) in the Airport Apron area International Yogyakarta Kulon Progo. This study used descriptive qualitative method. This research was carried out on March 1 – March 31 2023 at Yogyakarta Kulon Progo International Airport. The data collection techniques used in this research were documentation, observation and interviews with Apron Movement Control (AMC) Unit officers. Data analysis techniques use data reduction, data presentation, and drawing conclusions.The results of the research show that the handling carried out by the Apron Movement Control (AMC) unit is by checking. If there is Foreign Object Damage (FOD) scattered in the Apron area, it is immediately taken or stored in the Fod bin box and will later be handed over to the Safety Management System. (SMS). The obstacle faced by Apron Movement Control (AMC) unit officers at Yogyakarta Kulon Progo International Airport is the lack of awareness of operational officers in the Apron area, especially regarding order and cleanliness. There are several colleagues who are not optimally moving around the Apron so that Fod is not detected. External factors that cause Foreign Object Damage (FOD) on the Apron are objects brought in from outside such as flying grass from cuttings at the edge of the Apron or runway which are carried by the wind and enter the Apron. Meanwhile, the internal factors are plastic waste from GSE such as neat ropes, fragments of suitcases and from passengers.